Role of the Public Ministry in juvenile criminal justice (Legal journal - Research in Legal and Social Sciences, 2017)
Juvenile criminal justice has advanced in the defense of minors, in conflict with criminal law, since the approval of the Convention on the Rights of the Child in 1989, which establishes the paradigm of the comprehensive protection of children, girls and adolescents, whom it considers as subjects of rights, as opposed to the old guardianship system, which considered this population as an object of law. The States Parties to the Convention must establish specialized juvenile criminal jurisdiction, to favor access to justice without discrimination and apply the measure of preventive detention as a “last resort”. This research analyzes the extent to which the imposition of the custodial measure is required as a "last resort" in investigations carried out by ordinary criminal units, involving adolescent offenders of the criminal law. The documentary sample is selected, consisting of the judicial files of female adolescents, who were confined in the "Virgen de Fátima" Home in Asunción, in 2014. The review and analysis of said files was authorized by the general director of SENAAI, dependent on the Ministry of Justice. The quantitative, non-experimental descriptive method is applied. This investigation concludes that the preventive detention measure is not required as a "last ratio", because in most of the cases analyzed, it is observed that said measure is used as a rule and not as an exception.
Keywords: Paradigm; Principles; measures; Justice; role; ultima ratio